Performance of asphalt mixture by adding crumb rubber as modified bitumen - Nurhidayah, Abu Mansor Maturidi (2017)
The use of crumb rubber modified bitumen in asphalt mixture will beneficially in economy especially in Malaysia as we know that increment of waste crumb rubber will become serious issue over the world. Numerous studies have evaluated formulations design asphalt mixture to improve the environmental benefits and pavement performance using crumb rubber. In Malaysia, waste crumb rubber still being studied and may be will be major issue if nobody take action to recycle the scrap tire since the number of scrap tires steadily increased from year to year. Moreover, the inflation cost of bitumen and polymer modifiers and the lack of resources have motivated highway engineers to explore new material in the road pavement. Pavement problem and environmental problem which are majority came from waste rubber tire must be solved wisely. From the observation, the performance of asphalt mixes with different mixes with various percentage of crumb rubber added can be achieved. If the performances of asphalt mixture were found to be affected by the addition of modified crumb rubber, the optimum percentage of crumb rubber that enhances the properties of HMA mixes will be determined. In addition, Indirect Tensile Test was conducted to determine the contribution of crumb rubber in term of performance. From the test, the study was compared 1%, 2%, 3% of crumb rubber to 0% crumb rubber which is controlled sample to determine which percent closely to controlled sample. Based on the overall findings, the addition of 1% crumb rubber content which is close to the controlled sample was suggested in modifying the HMA mixes. Hence, 1% of crumb rubber content was determined as an optimum crumb rubber content. Thereby, the usage of crumb rubber in road construction should be put into consideration in order to provide pavement design with better durability and strength for further studies in the future. Finally, usage of crumb rubber as an alternative material will reduce cost by recycling waste material.